Exosomes as Novel Regulators of Adult Neurogenic Niches - Bátiz, Luis Federico; Castro, Maite A.; Burgos, Patricia V.; Velásquez, Zahady D.; Muñoz, Rosa I.; Lafourcade, Carlos A.; Troncoso-Escudero, Paulina; Wyneken, Ursula (Frontiers in Cellular Neuroscience, 2016)
Adult neurogenesis has been convincingly demonstrated in two regions of the mammalian brain: the sub-granular zone (SGZ) of the dentate gyrus (DG) in the hippocampus, and the sub-ventricular zone (SVZ) of the lateral ventricles. SGZ newborn neurons are destined to the granular cell layer of the DG, while new neurons from the SVZ neurons migrate rostrally into the olfactory bulb. The process of adult neurogenesis persists throughout life and is supported by a pool of neural stem cells (NSCs), which reside in a unique and specialized microenvironment known as “neurogenic niche”. Neurogenic niches are structured by a complex organization of different cell types, including the NSC-neuron lineage, glial cells and vascular cells. Thus, cell-to-cell communication plays a key role in the dynamic modulation of homeostasis and plasticity of the adult neurogenic process. Specific cell-cell contacts and extracellular signals originated locally provide the necessary support and regulate the balance between self-renewal and differentiation of NSCs. Furthermore, extracellular signals originated at distant locations, including other brain regions or systemic organs, may reach the niche through the cerebrospinal fluid or the vasculature and influence its nature. The role of several secreted molecules, such as cytokines, growth factors, neurotransmitters, and hormones, in the biology of adult NSCs, has been systematically addressed. Interestingly, in addition to these well-recognized signals, a novel type of intercellular messengers has been identified recently: the extracellular vesicles (EVs). EVs, and particularly exosomes, are implicated in the transfer of mRNAs, microRNAs (miRNAs), proteins and lipids between cells and thus are able to modify the function of recipient cells. Exosomes appear to play a significant role in different stem cell niches such as the mesenchymal stem cell niche, cancer stem cell niche and pre-metastatic niche; however, their roles in adult neurogenic niches remain virtually unexplored. This review focuses on the current knowledge regarding the functional relationship between cellular and extracellular components of the adult SVZ and SGZ neurogenic niches, and the growing evidence that supports the potential role of exosomes in the physiology and pathology of adult neurogenesis.